Comparative Study Between ‎Madrasah and Non-Madrasah ‎Institutions at the Upper ‎Secondary Level - Muhammad Ikram Fawwaz ‎; Riyan Maulana (CV Naskah Aceh, 2025)
This writing presents a comparison between the institutions a madrasah with non-madrasah agencies available in the area. Neither the madrasah nor non-madrasah institutions are actually as good. But it has its distinct preeminence between such agencies that makes its own appeal. The purpose of this writing was to find out why the madrasah educational institutions were more of a society than non-madrasah educational societies besides, becoming the favorite and whether the curriculum in madrasah educational institutions and non-madrasah education are the same or different. So we as writers are particularly interested in examining the comparative study between the madrasah and non-madrasah educational society. In this study the writers have used field research because the main data source used by the writers to take down the problem has to be collected in data fields, and to support it. In this article, the writer also uses other sources of literature, where the writers use various books, journals and research associated with this study.